(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
By studying of the collection of the National Herbarium of Ukraine (KW) – the Herbarium of the M.G. Kholodny Institute of Botany of the NAS of Ukraine – we found numerous authentic materials from the genus Acer L. (Sapindaceae) that served for O.H. Radde-Fomina for describe her new taxa, and that needing the clarification of their category. As a result of study these specimens, we lectotypificated four infraspecific names of Acer campestre L.: A. campestre subsp. austriacum (Tratt.) Radde-Fom. var. subintegrum Radde-Fom., A. campestre subsp. lobatum (Pax) Radde-Fom. var. parvifolium Radde-Fom., A. campestre subsp. lobatum (Pax) Radde- Fom. var. transiens Radde-Fom. and A. campestre subsp. marsicum (Guss.) Radde- Fom. var. schistosum Radde-Fom. For each taxa, the following data are provided: basionym; type according to the protologue, nomenclatural type and its location.